Neonatal outcome in maternal genital tract group B streptococcal colonization - Sharmila, Vijayan; Arun Babu, Thirunavukkarasu; Chaturvedula, Latha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: Group B streptococcus (GBS) is a leading cause of early onset neonatal infections and associated morbidity and mortality in the western world. The objective of this study was to assess neonatal outcome in maternal genital tract Group B streptococcal (GBS) colonization. Methods: Pregnant women with gestational age greater than 24 weeks were screened for vaginal GBS colonization during their regular visits to antenatal clinic. The vaginal swabs were inoculated in Todd Hewitt broth and later sub-cultured on blood agar for isolation of GBS. The patients were followed up till delivery. Neonatal characteristics like symptoms of clinical sepsis, screening tests for sepsis, culture positivity, low birth weight, preterm delivery and survival at 1 month were recorded and analyzed. Results: A total of 316 pregnant women were enrolled in the study. GBS was isolated from 7 patients (2.3%). A statistically significant increase in occurrence of PROM in women with GBS colonization was noted. However, none of the babies born to women with GBS colonization developed any clinical or proven sepsis, low birth weight or any other negative outcomes. Conclusions: GBS colonization rate was extremely low in our study. There was significant association between maternal genital tract colonization of GBS and occurrence of PROM. However, no neonatal adverse effects were found to be associated with GBS colonization in pregnancy.